Cognitive Impairment After COVID-19—A Review on Objective Test Data - Daroische, Rania; Hemminghyth, Mathilde S.; Eilertsen, Thomas H.; Breitve, Monica H.; Chwiszczuk, Luiza J. (Frontiers in Neurology, 2021)
Objective: The aim was to conduct a review on the literature on objective cognitive impairment in patients caused by COVID-19. Methods: We performed a literature review and searched Ovid Medline in February 2021 based on a PECO scheme. Results: Twelve articles met all inclusion criteria. Total patient sample was less than a thousand. All studies on global cognitive function found impairment, ranging from 15% to 80% of the sampled patients. Seven studies on attention and executive functions reported impairment, with varying results depending on sub-domain and different tests. Three out of four studies reported memory difficulties, with two studies reporting short-term memory deficits. Although results indicate possible language impairment, only one study used domain-specific language tasks. Two out of four studies on visuospatial function did not report any impairment. Conclusion: Patients with recent SARS-CoV-2 infection appear to experience global cognitive impairment, impairment in memory, attention and executive function, and in particular verbal fluency. Based on the current results, we recommend clinicians to evaluate the need for cognitive assessment of patients with a recent COVID-19 infection, regardless of the severity of the disease, treatment methods and length of ICU stay. We need studies with larger sample and control group.